The Impact of Problem-Based Student Worksheets on Improving Problem-Solving Skills in terms of Learning Outcomes - Oka Melawati; Evendi Evendi; Yusrizal Yusrizal; Irwandi Irwandi; A. Halim (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
The purpose of the study was to determine the impact of using a problem-based Student Worksheet (SWS) on improving problem-solving skills (PSS) in terms of student Learning Outcomes (LO). The research used a quantitative approach, quasi-experimental method, and the One Group Pretest-Posttest design research. The research sample also involved 31 high school students for the experimental class and 31 for the control class. The research has three variables: problem-based SWS, problem-solving skills (PSS), and Student Learning Outcomes (LO). The problem-solving skill instrument uses five essay questions, and the LO uses 20 multiple choice questions, both of which were developed by the researcher. Data analysis used the N-Gain formula to obtain information on the increase in PSS and LO. Based on the results of data analysis, it was found that the effect of implementing SWS was very significant on students’ PSS and LO. In addition, the application of SWS also affects students’ LO, and some students with high or low LO scores also have high PSS scores or vice versa. Inference from this study, it is hoped that teachers as educators will try to direct students to get used to solving physics problems using a five-stage problem-solving model.